AUTOMATED DESIGN OF OPTICAL SYSTEMS OF LENSES FOR SHORT-WAVE INFRARED RANGE - LAVRENUK, DARYNA; SOKURENKO, VYACHESLAV (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Cameras operating in short-wave infrared range (SWIR) are increasingly appearing in fields ranging from agriculture, food processing, and medical imaging to quality control, security/surveillance, automotive, and even archeology and art. Advanced SWIR cameras require SWIR lenses well-corrected for monochromatic and chromatic aberrations, with small F-numbers and high values of modulation transfer functions (MTF). In this research, a process of automated design of lens optical systems with a fixed focal length and high image quality for short-wave infrared range has been experimentally investigated. In particular, an automated aberration synthesis of two optical systems of SWIR lenses with spherical surfaces has been done: an 8-lens lens with the effective focal length of 50 mm, the relative aperture of 1:1.4 and the angular field of view of 23° and a 6-lens lens with the effective focal length of 200 mm, the relative aperture of 1:2.4 and the angular field of view of 5.87°. Both lenses are designed to operate in the short-wave infrared range (SWIR, 0.9–2.3 μm) with matrix image detectors having a diagonal up to 20.5 mm. In the synthesized systems, the values of the diffraction polychromatic modulation transfer functions are found greater than in the considered commercial lenses. The modified differential evolution algorithm was used to find the design parameters of the lenses. The performed aberration analysis of the synthesized SWIR lenses and the comparison of their characteristics with commercial lens samples indicate the high quality of the image and the competitiveness of the designed samples. Thus, the applied design technique makes it possible to generate original high-quality optical schemes of multi-lens lenses for the short-wave infrared range, taking into account the requirements and limitations established by the designer.